PARTISIPASI MASYARAKAT DALAM PERENCANAAN DAN PELAKSANAAN UNTUK PEMBANGUNAN FISIK DI DESA MEKAR RAYA KECAMATAN SIMPANG DUA KABUPATEN KETAPANG - Tedy E.01106121, Alfensus Marken John (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The purfose of this researeh is to know the role of society to the plysicel consruction of society participate in the planning and execution on the Mekar Raya villge of Simpang Dua subdistrict in Ketapang regen. By using qualitative method within descriptive approach on physicel coustruction in west borneo province still a lot of constraits. One of these is coused the participate of society in the village is not to fill expectation that is expected by sociaty and government. Based on this researeh, so to infrove the participate of society in physicel construction that will be done in the village. The village leander is desired to give the socialitation enough to society in planning, execution and contruetion advence. The village leader is desird cooperative wilh the pople so by itself realization of society can role to the plysicel construction.Â  The villages leander desired more resutute to make rules to keap and to function sical construction.Â Key word : participate planning, participate execution, sicel construction